EFEKTIVITAS PENYELESAIAN SENGKETA PAJAK MELALUI PROSES KEBERATAN DI KPP PRATAMA PALEMBANG ILIR BARAT TAHUN 2012-2014 - IKA SASTI FERINA; ERMADIANI .; WENI NURFITASARI (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2015)
This study used qualitative research and the data were collected through interviews, direct observing and documentation. The informants were obtained based on the consideration of the researcher.This research based on the objection from the Taxpayer because of there is differences opinion, misperception of regulation, the dereliction of Taxpayer and the length of time the issuance of the Objection Decision Letter by reviewers objection. Based on the research, it can give briefly understanding that the objection of tax cases which had done by Directorate General of Taxation South Sumatera and Bangka Belitung is properly correct with the procedure. Complaints resolution process conducted by Directorate General of Taxation South Sumatera and Bangka Belitung been very effective in resolving all cases of objections raised by the taxpayer listed on Tax Office Primary Palembang Ilir Barat because it can finish it within a period of less than twelve (12 ) months , even fastest time period is 4 months 5 days in 2014 , the date of filing of January 23, 2014 , and the date of issuance of the decision Objection May 28, 2014 so as to give a good impact on the quality / service quality and the Directorate General of Taxation South Sumatera and Bangka Belitung, but when viewed from the satisfaction of the taxpayer , the taxpayer wants the objection turnaround time can be accelerated so as to provide a legal certainty and satisfaction for the taxpayer on existing services.